Preliminary results on the study of 237Np(n,f) at n_TOF/EAR2 in energies related to nuclear waste transmutation - Stamatopoulos, Athanasios; the n_TOF Collaboration, and (HNPS Advances in Nuclear Physics, 2020)
The accurate knowledge of neutron-induced fission cross sections of isotopes involved in the nuclear fuel cycle is essential for the optimum design and safe operation of next generation nuclear systems. Such experimental data can additionally provide constraints for the adjustment of nuclear model parameters used in the evaluation process, resulting in a further understanding of the nuclear fission process. In this respect measurements of the 237Np(n,f) cross section have been performed at the n_TOF facility at CERN in the horizontal 185 m flight-path (EAR1) which were discrepant by 7% in the MeV region. The neutron-induced fission cross section of 237Np(n,f) was recently restudied at the EAR2 19.5 m vertical beam-line at CERN’s n_TOF facility, over a wide range of neutron energies, from 100 keV up to 15 MeV, using the time-of-flight technique and a modern set-up based on Micromegas detectors. This study was performed in an attempt to resolve the aforementioned discrepancies and to provide accurate data of a reaction that is frequently used as reference in measurements related to feasibility and design studies of advanced nuclear systems. Preliminary results with a high statistical accuracy that resolve the discrepancies will be presented along with a brief discussion concerning the facility and the analysis.